Role of Serine Proteases at the Tumor-Stroma Interface - Tagirasa, Ravichandra; Yoo, Euna (Frontiers in Immunology, 2022)
During tumor development, invasion and metastasis, the intimate interaction between tumor and stroma shapes the tumor microenvironment and dictates the fate of tumor cells. Stromal cells can also influence anti-tumor immunity and response to immunotherapy. Understanding the molecular mechanisms that govern this complex and dynamic interplay, thus is important for cancer diagnosis and therapy. Proteolytic enzymes that are expressed and secreted by both cancer and stromal cells play important roles in modulating tumor-stromal interaction. Among, several serine proteases such as fibroblast activation protein, urokinase-type plasminogen activator, kallikrein-related peptidases, and granzymes have attracted great attention owing to their elevated expression and dysregulated activity in the tumor microenvironment. This review highlights the role of serine proteases that are mainly derived from stromal cells in tumor progression and associated theranostic applications.